Pengembangan UMKM di Era Globalisasi: Laporan Pengabdian Masyarakat di Desa Dayeuhluhur-Ciamis - Aminullah, Rifqi Arief; Mubarrok, Dede Husni; Abdussalam, Agus; Firman, Ade; Dewi, Devi Riyanti; Nurshodiqoh, Samira (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2023)
Economic globalization is a process of global economic activity involving countries in the world. With free trade in the current era of economic globalization, UMKM are required to carry out appropriate strategies to win the competition. This research aims to find out how much UMKM know about the digital economy in the era of globalization which is so tight in the midst of economic globalization. In this research, researchers used descriptive qualitative methods with primary and secondary data sources, namely through observation, interviews and literature study. Based on the research results, it shows that there are still some UMKM who do not know the importance of the digital economy in today's UMKM, but there are also UMKM who know the system for implementing the digital economy in their businesses but are still limited in their knowledge of using the internet so they still have not implemented the digital economic system in their businesses.